2021
DOI: 10.3390/ijerph182312565
|View full text |Cite
|
Sign up to set email alerts
|

Implementing the Federal Smoke-Free Public Housing Policy in New York City: Understanding Challenges and Opportunities for Improving Policy Impact

Abstract: In 2018, the U.S. Department of Housing and Urban Development required public housing authorities to implement a smoke-free housing (SFH) policy that included individual apartments. We analyzed the policy implementation process in the New York City Public Housing Authority (NYCHA). From June–November 2019, we conducted 9 focus groups with 64 NYCHA residents (smokers and nonsmokers), 8 key informant interviews with NYCHA staff and resident association leaders, and repeated surveys with a cohort of 130 nonsmokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…The evidence presented here is restricted to the self-reports of PHA officials and lacks direct input from a wider range of PHA staff as well as PHA residents. These broader perspectives are critical to gain deeper insight into the complexity of smoke-free housing implementation experiences [ 35 ]. While a high proportion of PHAs reported resident engagement activities, we do not know whether those activities had high participation rates or how residents perceived them.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence presented here is restricted to the self-reports of PHA officials and lacks direct input from a wider range of PHA staff as well as PHA residents. These broader perspectives are critical to gain deeper insight into the complexity of smoke-free housing implementation experiences [ 35 ]. While a high proportion of PHAs reported resident engagement activities, we do not know whether those activities had high participation rates or how residents perceived them.…”
Section: Discussionmentioning
confidence: 99%
“…A pre- and post-study that evaluated the effects of the 2018 federal ban on smoking in public housing on air nicotine concentration levels in New York City public housing, found no significant difference in nicotine levels between living areas where the policy was in effect to areas where there was no policy [ 65 ]. In a mixed methods evaluation of the federal smoke-free public housing policy in New York City, residents saw limited enforcement of the ban in the year following its implementation [ 66 ]. Moreover, qualitative findings suggested that there would be resident and staff resistance to a mandated smoke-free policy [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a mixed methods evaluation of the federal smoke-free public housing policy in New York City, residents saw limited enforcement of the ban in the year following its implementation [ 66 ]. Moreover, qualitative findings suggested that there would be resident and staff resistance to a mandated smoke-free policy [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…A mixed methods study focusing on resident experiences pre and post policy implementation found residents still reported smoking violations 1 year after the policy was implemented. Participants in the study reported that the policy overreached by telling people what to do, was inconsistently enforced, and created the perception that smokers were being unfairly targeted given that other pressing housing issues were not addressed (42). Support for the policy remained unchanged for the study highlighting residents' willingness to accept the policy, but the nding of a decline in satisfaction with enforcement indicated a need to address contextual barriers to compliance (42).…”
Section: Introduction Background and Rationale {6a}mentioning
confidence: 99%
“…However, residents also expressed expectations of poor policy compliance due to lack of enforcement, safety concerns/inconvenience with smoking relocation, and general discontent with their housing authority and/or living conditions (39)(40)(41). Such concerns also remain consistent post policy implementation (42,43). A mixed methods study focusing on resident experiences pre and post policy implementation found residents still reported smoking violations 1 year after the policy was implemented.…”
Section: Introduction Background and Rationale {6a}mentioning
confidence: 99%